1989
DOI: 10.1038/bjc.1989.109
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour potential of pleural cavity macrophages in lung cancer patients without malignant effusion

Abstract: Summary The present study was undertaken to examine whether the presence of primary lung cancer could affect the antitumour activities of pleural cavity macrophages (PCM) and peripheral blood monocytes (PBM). PCM by pleural lavage and PBM were simultaneously obtained from 14 lung cancer patients not showing invasion of the pleural cavity. PCM and PBM were isolated by percoll gradient centrifugation and adherence. The lavage method yielded about 16.8 +9.6 (s.e.) x 106 cells, which consisted of 80.7% PCM, 17.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Data on the pleural lavage cytology are mainly derived from pathological effusion in tumor patients [14,15]. Limited information is available about the cellular composition of the pleural cavity in healthy humans.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the pleural lavage cytology are mainly derived from pathological effusion in tumor patients [14,15]. Limited information is available about the cellular composition of the pleural cavity in healthy humans.…”
Section: Discussionmentioning
confidence: 99%
“…Since human A375 melanoma cells were found to be susceptible to cytotoxicity by IL-1 and tumor necrosis factor (TNF) [18], one possibility is that the production of monokines (IL-1 and TNF) responsible for tumor cell killing may be regulated by different mechanisms, depending on the activation stimulus, the functional state or maturation of monocytes or the influence of cancer bearing. In fact, the productions of IL-1 and T N F are known to be regulated by differential mechanism [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…Itoh et al [11], for example, have reported cytolytic activity against fresh melanoma targets by unstimulated PBM, and Kimura et al [13] have shown that human PBM and alveolar macrophages can mediate cytotoxicity without deliberate activation. However, the enhancement of tumour cell growth by human PBM has not been reported extensively.…”
Section: Discussionmentioning
confidence: 97%